2023
DOI: 10.3389/fncel.2023.1130205
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of microglia function by neural stem cells

Abstract: Neural stem and precursor cells (NPCs) build and regenerate the central nervous system (CNS) by maintaining their pool (self-renewal) and differentiating into neurons, astrocytes, and oligodendrocytes (multipotency) throughout life. This has inspired research into pro-regenerative therapies that utilize transplantation of exogenous NPCs or recruitment of endogenous adult NPCs for CNS regeneration and repair. Recent advances in single-cell RNA sequencing and other “omics” have revealed that NPCs express not jus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 107 publications
0
2
0
Order By: Relevance
“…Further studies have shown human brain-derived NSCs (hNSCs) injected into the hippocampus of APP/PSEN1 model of AD, resulting in a development of neuronal connectivity and metabolic activity, which allowed for a decrease in AD pathogenesis [157]. Other than attenuating cognitive defects, NSCs can also inhibit inflammatory responses, neuronal loss, and regulation of microglia function [158,159].…”
Section: Neural Stem Cell Therapymentioning
confidence: 99%
“…Further studies have shown human brain-derived NSCs (hNSCs) injected into the hippocampus of APP/PSEN1 model of AD, resulting in a development of neuronal connectivity and metabolic activity, which allowed for a decrease in AD pathogenesis [157]. Other than attenuating cognitive defects, NSCs can also inhibit inflammatory responses, neuronal loss, and regulation of microglia function [158,159].…”
Section: Neural Stem Cell Therapymentioning
confidence: 99%
“…Radial glial cells, which are located in the VZ, generate neurons and maintain self-renewal through multiple rounds of asymmetric divisions (Misson et al, 1988;Noctor et al, 2001). Additionally, radial glial cells can generate intermediate progenitors, which translocate to the SVZ and undergo symmetric proliferation or neurogenic divisions (Noctor et al, 2001;Jayaraman et al, 2018;de Almeida et al, 2023).…”
Section: Aspm In Neurogenesismentioning
confidence: 99%
“…Glial cells secrete and deliver gliotransmitters, hormones, growth factors, cytokines, and nutrients and serve as a forerunner for neuroprogenitor cells [ 17 ]. They actively participate in neurophysiological processes including neurogenesis, synaptogenesis, synaptic plasticity, synaptic transmission, and neuronal survival [ 18 ]. Glial cells are the earliest defenders of the CNS, as they substantially promote the preservation of BBB integrity.…”
Section: Introductionmentioning
confidence: 99%